Figure Concept and Method - Lury, Celia; Viney, William; Wark, Scott (Springer Nature, 2022)
This open access book shows how figures, figuring, and configuration are used to understand complex, contemporary problems. Figures are images, numbers, diagrams, data and datasets, turns-of-phrase, and representations. Contributors reflect on the history of figures as they have transformed disciplines and fields of study, and how methods of figuring and configuring have been integral to practices of description, computation, creation, criticism and political action. They do this by following figures across fields of social science, medicine, art, literature, media, politics, philosophy, history, anthropology, and science and technology studies. Readers will encounter figures as various as Je Suis Charlie, #MeToo, social media personae, gardeners, asthmatic children, systems configuration management and cloud computing - all demonstrate the methodological utility and contemporary relevance of thinking with figures. This book serves as a critical guide to a world of figures and a creative invitation to "go figure!"